Vitalitative differentiation as a prerequisite for the polyalternativeness of development in natural populations Homogyne alpina (Asteraceae) of Chernogora (Carpathians) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The state, demographic dynamics, ontogenesis and the duration of its stages have been studied in the populations of the Homogyne alpina of Chernogory (the Carpathians). The article is devoted to new aspects and interpretation of the phenomenon of polyvariance in the development of populations of herbaceous perennials. The results are based on long-term stationary research and monitoring at permanent test sites of the Institute of Ecology of the Carpathians. It is shown that the principles of development of populations of H. alpina are formed under the influence of dominants of plant communities. The polyvariance of the ontogenesis of populations is interpreted as a result of adaptive changes in their vital structure. The article summarizes typical variants of ontogenesis of the H.a alpina. It is concluded that the pattern of population development is the result of ratios and abundance among passive and active individuals. The role of generative reproduction in the sustainability of H. alpina populations has been substantiated. Data are presented on the duration of ontogeny in the phytocenoses of the Carpathians depending on the vital structure of the population. It has been established that it is differentiated by vital groups (high, medium and low). As the vital structure deteriorates, the speed of ontogenesis slows down. And this is also accompanied by changes in the overall strategy for the development of populations in general. The author of the article believes that the general auto-correction of populations of herbaceous plants is carried out precisely on such principles. It has been shown that the sustainability of H. alpina populations is determined by their ability to change life cycles in accordance with environmental conditions. The belt of spruce forests and shrub biogeocoenoses is defined as the zone of autoecological optimum for the H. alpina populations. Separately, the functional role of individuals that are in a state of deep rest is discussed. For this reason, they do not participate in population resumption processes. But they form a population reserve, important for restoring the optimal population structure at critical moments in their lives.
Keywords: morphogenesis, ontogenesis, ontogenetic structure, vitality structure vitality, vital state, natural population.